Mecanismos de atenuación en español e inglés. Implicaciones pragmáticas en la cortesía - Ballesteros Martín, Francisco José (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This article aims to be an extension of the results presented in Ballesteros 2001. The analysis carried out there revealed that politeness is a culture-specific value which depends on the prevailing ethos of each society. Mitigation is an optional tool in order to soften the impositive force of a requestive act whose redressive function is exploited by many speakers who intend to be polite. The concern of this article will be the mitigating function of two kinds of devices: lexical or phrasal downgraders on the one hand, and syntactic downgraders on the other. The presence of such devices will be compared in the request realizations of two national samples constituted by Spanish and British native speakers.The requestive patterns have been extracted from sociopragmatically different situations. Among the issues to be considered are the specification of how contextual factors such as the interlocutors’ role, their rights and obligations, and the degree of imposition involved in the act influence the choice of lexical and syntactic downgraders. The conclusion is that mitigation cannot be considered a totally transferable phenomenon in both languages. The pragmatic implications derived from the observed variation in degree of usage and frequency in both corpora are also assessed.